2022
DOI: 10.21608/sinjas.2022.142797.1103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Productive Performance in Synthetic Maternal Line (Apri Rabbits) Under Egyptian Conditions

Abstract: Synthetic lines have been developed in hot climate countries over the last few decades through selection for specific goals such as APRI rabbits, and depending on their specialisation, these lines perform better than the standard of the original breeds, and contemporary production tends to rely on them. The aim of the study was to identify and explain genetic parameters in synthetic maternal line (APRI rabbits) under Egyptian conditions. (DFREML) was used to assess data on body weights (BW) at 4, 8, and 12 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Also, the ranges in PBV's for daily weight gains were high and ranging from 9.9 to 26.6 g for DG4-6, 7.8 to 18.3 g for DG6-8, 9.4 to 16.9 g for DG8-10 and 11.2 to 16.3 g for DG10-12. Similarly, the reviewed estimates of PBV for post-weaning body weights and daily weight gains cited in an Egyptian study showed that the ranges in PBV's were high and ranging from 175 to 221 g for BW4, 72 to 264 g for BW6, 69 to 299 g for BW8, 148 to 420 g for BW10 and 179 to 660 g for BW12 (El-Deghadi et al, 2023).…”
Section: Predicted Breeding Values (Pbv)mentioning
confidence: 99%
“…Also, the ranges in PBV's for daily weight gains were high and ranging from 9.9 to 26.6 g for DG4-6, 7.8 to 18.3 g for DG6-8, 9.4 to 16.9 g for DG8-10 and 11.2 to 16.3 g for DG10-12. Similarly, the reviewed estimates of PBV for post-weaning body weights and daily weight gains cited in an Egyptian study showed that the ranges in PBV's were high and ranging from 175 to 221 g for BW4, 72 to 264 g for BW6, 69 to 299 g for BW8, 148 to 420 g for BW10 and 179 to 660 g for BW12 (El-Deghadi et al, 2023).…”
Section: Predicted Breeding Values (Pbv)mentioning
confidence: 99%